2020
DOI: 10.1002/edm2.132
|View full text |Cite
|
Sign up to set email alerts
|

Footwear and insole design features for offloading the diabetic at risk foot—A systematic review and meta‐analyses

Abstract: The aim of this systematic review was to identify the best footwear and insole design features for offloading the plantar surface of the foot to prevent foot ulceration in people with diabetic peripheral neuropathy. We searched multiple databases for published and unpublished studies reporting offloading footwear and insoles for people with diabetic neuropathy and nonulcerated feet. Primary outcome was foot ulcer incidence; other outcome measures considered were any standardized kinetic or kinematic measure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 79 publications
1
29
0
2
Order By: Relevance
“…A recent review of Collings et al 2020 [ 17 ] highlighted the difficulty in differentiating the effect of the different insole and footwear features in offloading the NDF. However, they found that arch profiles, metatarsal additions, and apertures are effective in reducing plantar pressure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent review of Collings et al 2020 [ 17 ] highlighted the difficulty in differentiating the effect of the different insole and footwear features in offloading the NDF. However, they found that arch profiles, metatarsal additions, and apertures are effective in reducing plantar pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Foot orthotics are mostly evaluated based on clinical experience and a trial-and-error approach [ 11 ]. Conversely, studies introducing the routinely use of quantitative plantar pressure measurement-driven directions for effectively offloading insoles are increasingly presented in the literature [ 2 , 3 , 7 , 5 , 8 14 , 17 ]. Several studies have investigated the offloading effects either induced by elevating pressures in areas of lower pressure (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations